2019
DOI: 10.1111/ijac.13204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sintering temperature on microstructure, properties, and crushing behavior of ceramic proppants

Abstract: Ceramic proppants with excellent performance were successfully prepared by second grade bauxite. The phase structure and the microstructure were investigated via X-Ray diffraction and scanning electron microscopy. The results suggested that bulk density and apparent density constantly increased, while the breakage ratio gradually decreased with the increasing in sintering temperature. When the sintering temperature reached to 1500°C, the breakage ratio obtained lowest value of 3.6% under 52 MPa closed pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It was shown that the increase in temperature led to the open porosity decreased from 31% to 25%, this decrease is probably related to some open pores that were closed during heating. The decreasing of the open porosity may also contribute to the densification of the material 40,42 . The higher increase in thermal conductivity compared to the increase observed for the compressive strength in the range 1000 to 1200°C for NZ2 could be justified by the occurrence of crystalline phases with higher intrinsic thermal conductivity upon firing like mullite.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was shown that the increase in temperature led to the open porosity decreased from 31% to 25%, this decrease is probably related to some open pores that were closed during heating. The decreasing of the open porosity may also contribute to the densification of the material 40,42 . The higher increase in thermal conductivity compared to the increase observed for the compressive strength in the range 1000 to 1200°C for NZ2 could be justified by the occurrence of crystalline phases with higher intrinsic thermal conductivity upon firing like mullite.…”
Section: Resultsmentioning
confidence: 96%
“…The decreasing of the open porosity may also contribute to the densification of the material. 40,42 The higher increase in thermal conductivity compared to the increase observed for the compressive strength in the range 1000 to 1200°C for NZ2 could be justified by the occurrence of crystalline phases with higher intrinsic thermal conductivity upon firing like mullite.…”
Section: Characteristics Of Raw Materialsmentioning
confidence: 95%
“…In addition, it can be found that the effect of increasing the same fracture surface energy at high temperatures is better than that at normal temperatures. Studies have shown that increasing sintering temperature 26 or adopting a two‐step sintering process 27 can reduce the porosity of materials, improve the density of materials, and thus improve the fracture surface energy of materials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as indicated in Figure 2, in the nitrogen environment, the prediction results of the two methods are again consistent with the experimental data at 1400°C, the experimental data in the nitrogen environment is much lower than the experimental data in Figure 1 in the air environment, which again confirms the above statement. Further, to facilitate comparison, the prediction results of Deng 20 , ACK 11 , and Marshall and Cox combined with TA B L E 2 Material parameters for different fiber-reinforced ceramic matrix composites (FRCMCs) 10,16,22,[25][26][27][28][29] 2 and 3. As indicated in Figure 3 that the prediction results of the models are in good agreement with the measurement results.…”
Section: Sic F /Rbsn Compositesmentioning
confidence: 99%
“…Proppants are solid, spherical, millimeter-sized particles which play a critical role in the hydraulic fracturing of oil and gas, especially in the development of non-conventional oil and gas resources [ 2 , 3 ]. The quality of the proppant and the pattern of their placement directly determines the stimulation efficiency of the hydraulic fracturing treatment [ 4 , 5 ]. Proppants should have sufficient strength to keep cracks open that will form channels to make the oil and gas flow through conveniently, causing the well production to be increased significantly [ 6 ].…”
Section: Introductionmentioning
confidence: 99%